Prescribing pattern of antidepressants in psychiatric unit of a tertiary care hospital - Avanthi, E.; Somashekar, H. S.; Kumar, L. Pradeep; Sushma, H. K.; Sudarshan, C. Y.; Raja, Babbol (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective was to study the prescribing pattern of antidepressants in psychiatric unit of a tertiary care hospital. Methods: An observational study was carried out at psychiatry out-patient department (OPD). The data which were collected included information about age, gender, education, occupation, marital status and drug prescription included trade name, generic name, dosage, and frequency of 100 outpatients who attended the psychiatry OPD. Results: Among 100 patients with major depression 66% were females and 34% were males. Depression was more commonly seen between patients with age group 21-40 years. Depression was more common among housewives (44%) and next was students (18%). Percentage of depression was more in educated people with (72%) than in uneducated with (28%). Depression was more commonly seen in married people with (77%) than in unmarried people (23%). Most commonly prescribed antidepressant as monotherapy was fluoxetine and as combination therapy was fluoxetine and escitalopram. Conclusions: Depression is more commonly seen in married people predominantly in females and housewives. Fluoxetine is more commonly used followed by escitalopram. Selective serotonin reuptake inhibitors are preferred over other antidepressant because of their relative lesser side effects.